The Jews of the Middle East and North Africa - Simon, Reeva S., author.
1 online resource
Keywords: "Incorporating published and archival material, this volume fills an important gap in the history of the Jewish experience during World War II, describing how the war affected Jews living along the southern rim of the Mediterranean and the Levant, from Morocco to Iran. Surviving the Nazi slaughter did not mean that Jews living in the Middle East and North Africa were unaffected by the war: there was constant Antisemitic propaganda and general economic deprivation; communities were bombed; and, Jews suffered because of the Vichy Antisemitic regulations that left them unemployed, homeless and subject to forced labor and deportation to labor camps. Nevertheless, they fought for the Allies and assisted the Americans and the British in the invasion of North Africa. These men and women were community leaders and average people who, despite their dire economic circumstances, worked with the refugees attempting to escape the Nazis via North Africa, Turkey, or Iran and connected with international aid agencies during and after the war. By 1945, no Jewish community had been left untouched and many were financially decimated, a situation that would have serious repercussions on the future of Jews in the region. Covering the entire Middle East and North Africa region this book on World War II is a key resource for students, scholars and general readers interested in Jewish history, World War II and Middle East history"--